New species and new records of millipedes of the genera Nepalmatoiulus Mauriès, 1983 and Anaulaciulus Pocock, 1895 (Diplopoda, Julida, Julidae) from mainland China - Mikhaljova, Elena V. (Zootaxa, 2024)
Four new species of the millipede genus Nepalmatoiulus Mauriès, 1983 and one of Anaulaciulus Pocock, 1895 (Julida, Julidae) are described from Yunnan Province in China: N. davidiani sp. nov., N. jianchuanensis sp. nov., N. lancangensis sp. nov., N. shiguensis sp. nov. and A. shibaensis sp. nov. New faunistic records are given for N. deqenensis Mikhaljova, 2020b and N. tuoxiaensis Mikhaljova, 2023a. Taxonomic remarks are provided for nearly all new species. The occurence of Anaulaciulus inaequipes Enghoff, 1986 in China is being questioned.